Tablets as an educational tool for enhancing preschool science - Furman, Melina Gabriela (2018)
Information communication technologies (ICT) is increasingly being introduced in the preschool level, but questions have been raised regarding its potential to develop content knowledge or specific skills. This quasi-experimental study looked into the impact that hand-held tablets can have on science learning outcomes in five-year-olds. Four classes from two preschool institutions in Buenos Aires, Argentina, were selected for a six-week intervention. All four classes received training and an inquiry-based science teaching sequence, with one group from each institution also receiving tablets and specific guidance on how to incorporate them into their science lessons. Post-intervention test results showed significant improvements in science outcomes for all students, but no significant difference between the tablet-enhanced classrooms and those taught without ICT. Challenges and opportunities are discussed with regard to including tablets for teaching science at the preschool level.